THE EFFECT OF GADGET BAN POLICY ON STUDENTS' LEARNING MOTIVATION AND SOCIAL BEHAVIOR AT SMPN 1 LEMBANG, WEST BANDUNG REGENCY - Dinna Daniati; Lili Halimah; Khaerul Syobar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates the effect of a school-level gadget ban policy on the learning motivation and social behavior of students at SMPN 1 Lembang, West Bandung Regency. In the digital era, uncontrolled smartphone usage has led to cognitive distraction, reduced attention spans, and an increase in negative social interactions such as cyberbullying among adolescents. Utilizing an explanatory quantitative approach with a cross-sectional design, data were collected from 302 students selected through proportionate stratified random sampling. The primary instrument was a valid and reliable Likert-scale questionnaire, supported by structured observation and documentation. Data were analyzed using simple linear regression. The results indicate that the gadget ban policy, implemented through a strict